2006
DOI: 10.1007/s11127-005-9003-y
|View full text |Cite
|
Sign up to set email alerts
|

Government Size and Unemployment: Evidence from Industrial Countries

Abstract: Using data from 19 industrial countries for the period 1985 to 2002, this paper analyzes how the size of the government sector affects unemployment. Controlling for the impact of the business cycle as well as for the impact of all major labor market institutions and unobserved country effects, we find that a large government sector is likely to increase unemployment. It appears to have a particularly detrimental effect on women and the low skilled and to substantially increase long-term unemployment. It seems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
1
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 20 publications
5
27
1
5
Order By: Relevance
“…Higher values on the 0-10 scale represent lower marginal tax rates and higher income thresholds. Previous studies have found that a heavy tax burden is likely to lower employment and to increase unemployment (see, e.g., Prescott 2004;Feldmann 2006a). 8 8 The tax burden on labor ('tax wedge') would have been a preferable indicator.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Higher values on the 0-10 scale represent lower marginal tax rates and higher income thresholds. Previous studies have found that a heavy tax burden is likely to lower employment and to increase unemployment (see, e.g., Prescott 2004;Feldmann 2006a). 8 8 The tax burden on labor ('tax wedge') would have been a preferable indicator.…”
Section: Datamentioning
confidence: 99%
“…The EFW indicator 'top marginal tax rate' can be regarded as a proxy for the tax burden on labor, because countries with a large (small) tax wedge usually also have a high (low) top marginal income and payroll tax rate and a low (high) income threshold at which the top marginal income tax rate applies. Besides, Feldmann (2006a) indicates that high top marginal income and payroll tax rates and low income thresholds at which top marginal income tax rates apply exert a detrimental impact of their own on unemployment in industrial countries.…”
Section: Datamentioning
confidence: 99%
“…However, assorted results were observed due to the country or countries researched, methods used and the data employed. Research conducted in developed countries includes the work of Rose (1981), Tanzi and Zee (1997), Fatas and Mihov (1998), Abrams (1999), Kneller, Bleaney and Gemmell (1999), Hercowitz andStrawczynski (2004), andFeldmann (2006). To examine the relationship between fiscal policy and the behaviour of unemployment in developing countries, various researches have also been conducted.…”
Section: A Review Of Supporting Literaturementioning
confidence: 99%
“…As higher values on the scale represent lower marginal tax rates and higher income thresholds, we label this variable 'low top marginal tax rate.' Previous studies have found that a heavy tax burden is likely to lower employment and to increase unemployment in industrial countries (for example, Prescott, 2004;Feldmann, 2006a). 9 To control for business cycle fluctuations, we normalized each country's GDP growth rate for its trend growth rate.…”
Section: Dependent Variables Control Variables and Estimation Methodsmentioning
confidence: 99%